Stringent Response and AggR-Dependent Virulence Regulation in the Enteroaggregative Escherichia coli Strain 042 - Hüttener, Mário; Prieto, Alejandro; Espelt, Joan; Bernabeu, Manuel; Juárez, Antonio (Frontiers in Microbiology, 2018)
Virulence expression in the enteroaggregative E. coli strain 042 requires the transcriptional activator AggR. We show in this report that, as reported for other virulence factors, the nucleotide second messenger (p)ppGpp is needed for a high expression level of AggR. As expected from these findings, expression of AggR-activated genes such as the AafA pilin subunit is downregulated in the absence of (p)ppGpp. Considering the fact that biofilm formation in strain 042 requires the AafA protein, biofilm development in strain 042 is impaired in derivatives that lack either the AggR protein, the virulence plasmid that encodes AggR (pAA2) or the ability to synthesize (p)ppGpp. These results show a direct correlation between (p)ppGpp, expression of AggR and biofilm development in strain 042.